1993
DOI: 10.1159/000213544
|View full text |Cite
|
Sign up to set email alerts
|

The Event-Related P300 Potential Analysis of Cognitive Human Brain Aging: A Review

Abstract: Event-related P300 potentials are closely reflecting cognitive functions such as stimulus evaluation time (P300 latency) and task relevance (P300 amplitude). Hence, both their potential clinical application for detecting slight cognitive disturbances and an increasing interest in the aging of cognitive human brain functions resulted in a growing number of studies on age-related P300 changes. Although there are converging lines of evidence that aging results in prolongations of P300 latencies, reductions of P30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 46 publications
7
53
1
1
Order By: Relevance
“…Some authors reported that the central nervous system is mature only at the age of 17 years, owing to the process of neurological maturation (Buchwald, 1990 3 ), in which there is increase in intra and inter-cortical connectivity, as reported 16 . However, it is believed that P300 may be carried out in children as of the age of 7.…”
Section: Discussionmentioning
confidence: 88%
“…Some authors reported that the central nervous system is mature only at the age of 17 years, owing to the process of neurological maturation (Buchwald, 1990 3 ), in which there is increase in intra and inter-cortical connectivity, as reported 16 . However, it is believed that P300 may be carried out in children as of the age of 7.…”
Section: Discussionmentioning
confidence: 88%
“…One might wonder whether our ERP effects are more related to the P300, a complex of ERP modulations that has been related to stimulus probability, subjective confidence, and target detection (Donchin and Coles, 1988;Johnson, 1993;Kugler et al, 1993;Polich and Kok, 1995;Squires et al, 1976). Although the later temporal peak of the probability effect is consistent with this speculation, several considerations suggest that the probability-related ERP modulations are more closely related to the FRN than to the P300.…”
Section: Win-related But Not Loss-related Erps Were Modulated By Fementioning
confidence: 80%
“…For instance, a classical hypothesis in neurocognitive aging research states that the aging brain is noisier [42], due to deteriorations in various transmitter systems [1,2,13,15,35,36,45], such as acetylcholine (Ach) and monoamines (e.g., dopamine, norepinephrine, and serotonin), and degenerations in structural integrity, such as reductions in gray and white matter density and brain volume shrinkages in prefrontal cortex and hippocampus [4,33] as well as attenuated functional connectivity between these cortical regions [11]. Brain electrophysiological activities captured by EEG recordings show aging-related increase in variability [16]. Noisy fluctuations in cognitive and sensorimotor processes also increase with aging [19,22,23,27].…”
Section: Introductionmentioning
confidence: 99%